The Power of Camaraderie: Conference Engagement for BIPOC Nurses in Academia. - Carter, Erik V.; Stephens, Umeika; Walker, Tara; McNeill, Cynthera; Bowman, Angela; Jenkins, Randon; Fletcher, Audwin B. (ABNFF Journal, 2026)
Background BIPOC (Black, Indigenous, and People of Color) nurses remain underrepresented in academia and often experience isolation and limited mentorship. Academic conferences can help counter these barriers by fostering camaraderie and a sense of belonging. Methods A narrative review of English-language, peer-reviewed literature (January 2020 through March 2025) and historical sources examined mentorship, professional development, and conference participation among BIPOC nurses in academic settings. Results Affinity-based conference engagement reduced isolation, strengthened mentorship, and promoted culturally responsive teaching and leadership, but institutional barriers --especially funding and structural support--limited participation and impact. Implications Academic leaders should prioritize funding and sustained support for affinity-based conferences and mentorship programs as evidence-based strategies to improve faculty development and student outcomes. Conclusions Institutional investment in belonging, mentorship, and professional engagement enhances equity, retention, and excellence in nursing education.